(untitled) (African Human Mobility Review, 2021)
This paper examines the relationship between internal migration, socioeconomic status and remittances, drawing on the experiences of migrant adolescent girl head porters in the cities of Accra and Kumasi in Ghana. Through an explanatory sequential mixed methods research design involving 503 individual surveys and 24 in-depth interviews, the paper established that 61% of adolescents studied migrated from the north to the south to escape poverty while 29% migrated to work and raise money for school fees. The kayayoo business does not seem to capacitate the adolescent girls to live the kind of lives they have reason to value because only 36% of them remitted to their families. A logistic regression model showed that older adolescents, 15- 19 years, (AOR=7.32, p<0.05, CI= [1.999-26.802] number of years spent working as head porter, 3-years, (AOR=3.97, p<0.05, CI= [1.633-9.677] and socio-economic status – not poor (AOR=8.63, p<0.001, CI=[4.761-8.435]) significantly influenced remittances. Remittances capacitated recipient families to invest in human capital development and also improved household food security.